EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM MENSEJAHTERAKAN MASYARAKAT MISKIN DI DESA LAWINDRA KECAMATAN UMBUNASI KABUPATEN NIAS SELATAN - Tafonao, Kamurnian; Tobing, Artha Lumban; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The purpose of this study was to determine the effectiveness of the Family Hope Program (PKH) in improving the welfare of the community in Lawindra Village, Umbunasi District using descriptive qualitative research methods and data sources obtained through interviews and documentation studies. The informants in this study were village heads, beneficiary communities of the Family Hope Program (PKH). The results of this study are that the effectiveness of the Family Hope Program (PKH) in Lawindra Village, Umbunasi District, South Nias Regency is running smoothly and in accordance with existing regulations and the role of the village government there in a good perspective as evidenced by the statements of some of the people they interviewed said that the service from village government officials there is quite good, the inhibiting factors for the Effectiveness of the Family Hope Program (PKH) in Lawindra Village in the process of collecting data on PKH program beneficiaries, technical assistants to PKH, technical distribution/distribution, and use of PKH program funds, supporting factors in the implementation of the PKH program are the provision of Automated Teller Machines (ATMs) and individual account books for PKH beneficiaries. As for the suggestions from the author in the distribution of the Family Hope Program (PKH) the administrators pay more attention to it so that the assistance provided is right on target